Impact of Preserved Myocardial Contractile Function in the Segments Attached to the Papillary Muscles on Reduction in Functional Mitral Regurgitation. Issue 2 (20th November 2012) - Tatsumi, Kazuhiro; Tanaka, Hidekazu; Kataoka, Toshiya; Norisada, Kazuko; Onishi, Tetsuari; Kawai, Hiroya; Hirata, Ken‐ichi
<x xml:space="preserve">Abstract</x> Background: Effectiveness of functional mitral regurgitation (FMR) in heart failure patients is of growing importance for patient prognosis. The purpose of this study was to investigate whether regional myocardial contractile function as assessed by tissue Doppler strain rate imaging can predict reduction in FMR caused by dobutamine. Methods: Fifty‐one patients with depressed left ventricular (LV) ejection fraction (32 ± 9%) secondary to dilated cardiomyopathy and FMR underwent evaluation of effective regurgitant orifice (ERO) of FMR, mitral valve deformation, global LV remodeling, and regional myocardial contractile function assessed by longitudinal peak systolic strain rate (Ssr) in 6 mid‐LV segments from standard apical views. We also determined the average Ssr of segments attached to the papillary muscles, that is, the inferior, inferolateral, and anterolateral segments (PM segments Ssr). Low‐dose (10 μg/kg per minute) dobutamine‐induced reduction in ERO was compared with baseline variables. Results: Baseline valve tenting was associated with dobutamine‐induced reduction in ERO (r = −0.30, P < 0.05). Receiver operating characteristic curve analysis showed that baseline valve tenting, LV sphericity index, inferior Ssr, inferolateral Ssr, and PM segments Ssr were predictors of dobutamine‐induced ≥30% reduction in ERO. Importantly, only PM segments Ssr predicted dobutamine‐induced ≥20% reduction in valve tenting with area under the curve of 0.67 (P < 0.05). Conclusions: Preserved myocardial contractile function in the segments attached to the PMs was associated with dobutamine‐induced reduction in mitral valve tenting and FMR, suggesting that our findings are important for improvement in cardiac function and FMR with medical treatment.